Positron Annihilation Spectroscopy in Material studies - Horodek, P.; Khiem, L. H.; Siemek, K.; Tuyen, L. A.; Kobets, A. G. (Communications in Physics, 2019)
Positron annihilation spectroscopy (PAS) is a method dedicated to detection of open-volume type of defects in materials. Nowadays, this technique is of a great interest due to the practical character of obtained results. New devices using monoenergetic positron beams are built. The paper presents the basics of PAS, a description of popular experimental techniques and their application on the basis of results obtained in the frame of collaboration between Joint Institute for Nuclear Research (JINR), Institute of Physics - Vietnamese Academy of Science and Technology (VAST) and Vietnam Atomic Energy Institute (Vinatom).. The positron beam with energy up to 35 keV and other apparatus for PAS studies are under operation in Dubna.